2022
DOI: 10.1002/ijc.34238
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of genomic and radiologic features reveals distinct driver patterns of RTK/RAS pathway in ground‐glass opacity pulmonary nodules

Abstract: Ground-glass opacity (GGO)-associated pulmonary nodules have been known as a radiologic feature of early-stage lung cancers and exhibit an indolent biological behavior. However, the correlation between driver genes and radiologic features as well as the immune microenvironment remains poorly understood. We performed a custom 1021-gene panel sequencing of 334 resected pulmonary nodules presenting as GGO from 262 Chinese patients. A total of 130 multiple pulmonary nodules were sampled from 58 patients. Clinical-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Furthermore, research has demonstrated that, as the GGN solid component increases, the mutation frequency of EGFR , KRAS and TP53 increases ( 93 ). Notably, KRAS mutations are associated with a higher rate of CD8 + T cell infiltration, stronger proliferative and immunosuppressive signals ( 92 , 102 , 104 ). ALK mutations are more frequently observed in young adults and are mainly diagnosed at an advanced tumor stage ( 100 , 105 , 106 ).…”
Section: Genomic Characterization Of Sub-centimeter Lung Cancermentioning
confidence: 99%
“…Furthermore, research has demonstrated that, as the GGN solid component increases, the mutation frequency of EGFR , KRAS and TP53 increases ( 93 ). Notably, KRAS mutations are associated with a higher rate of CD8 + T cell infiltration, stronger proliferative and immunosuppressive signals ( 92 , 102 , 104 ). ALK mutations are more frequently observed in young adults and are mainly diagnosed at an advanced tumor stage ( 100 , 105 , 106 ).…”
Section: Genomic Characterization Of Sub-centimeter Lung Cancermentioning
confidence: 99%
“…Deciphering the driving factors underlying this process is of paramount importance as they hold potential diagnostic and therapeutic implications. Distinct gene mutations exhibit diverse biological behaviors, with studies demonstrating that EGFR and KRAS mutations are associated with aggressive and rapid growth of these nodules [51][52][53][54]. EGFR mutations represent the most prevalent and primary driving force behind early disease progression [51,55].…”
Section: Progress and Feasibility Of Targeted Therapymentioning
confidence: 99%
“…Distinct gene mutations exhibit diverse biological behaviors, with studies demonstrating that EGFR and KRAS mutations are associated with aggressive and rapid growth of these nodules [51][52][53][54]. EGFR mutations represent the most prevalent and primary driving force behind early disease progression [51,55]. Nodules harboring BRAF, ERBB2, and MAPK2P1 mutations exhibit an indolent behavior and a higher likelihood of being classified as partsolid ground-glass nodules [51], The absence of EGFR, KRAS, ALK and HER2 mutations was found to be associated with no growth in GGN.…”
Section: Progress and Feasibility Of Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although multicentric origin was predominant, they also detected early metastatic events among multifocal SSNs. Similarly, Yu et al (78) performed a custom 1021-gene panel sequencing of 334 resected pulmonary nodules presenting as GGO from 262 Chinese patients. They compared gene pathways enriched in different GGOs (pure GGOs and mixed GGOs) through genomic profiling.…”
Section: The Distinction Between Mplc and Ipmmentioning
confidence: 99%